The Risk Factors for Benign Breast Diseases: A Literature Review - He, Jiawen (International Journal of Public Health and Medical Research, 2026)
Benign breast diseases (BBDs) are a group of heterogeneous, non-malignant breast conditions that affect many women around the world. It is associated with the risk of breast cancer. However, the evidence of the risk factors for BBDs is inconsistent. This review aimed to synthesize the existing evidence on the risk factors of overall BBD and its subtypes, including non-proliferative diseases, proliferative diseases (proliferative diseases without atypia and atypical hyperplasia). A comprehensive search was conducted in the Embase database for studies that evaluate the associations between various risk factors and BBDs. Twenty-one eligible articles were included. Due to the high heterogeneity of the included articles, this study adopted a narrative synthesis approach. The results showed that multiple dietary and lifestyle factors were associated with the risk of overall BBD, including alcohol consumption, tanning bed use, body mass index, height, family fat, vegetable protein, fiber, nuts, etc. For non-proliferative diseases, alcohol consumption was associated with an increased risk, while the intake of vitamin E and dietary fiber may have negative association. For proliferative BBD, vitamin E and fiber both showed a negative association, while alcohol consumption was associated with an increased risk. Caffeine intake may increase the risk of atypical hyperplasia. In summary, this review indicates that the risk factors may vary across subtypes of BBD, although the evidence for certain BBD subtypes remains limited. Therefore, BBD should not be treated as a single disease entity in future studies. Subtype-specific investigations are recommended to better clarify the etiology of BBDs.